Rural women and food and agricultural technology in Modern Peru - Loayza Alatrista, Sulema (2017)
This study analyzes ongoing processes occurring in certain sectors of local food production, which are influenced by globalized and fluctuating markets that have rediscovered Andean foods. These small food producers are incorporating new technologies into agricultural practices, food production, and product commercialization. This research attempts to identify the economic, cultural and institutional factors that influence the adoption of new technologies by rural women.